2008
DOI: 10.1124/mol.108.050773
|View full text |Cite
|
Sign up to set email alerts
|

Different Interactions between MT7 Toxin and the Human Muscarinic M1 Receptor in Its Free and N-Methylscopolamine-Occupied States

Abstract: Muscarinic MT7 toxin is a highly selective and potent antagonist of the M 1 subtype of muscarinic receptor and acts by binding to an allosteric site. To identify the molecular determinants by which MT7 toxin interacts with this receptor in its free and NMS-occupied states, the effect on toxin potency of alanine substitution was evaluated in equilibrium and kinetic binding experiments as well as in functional assays. The determination of the crystallographic structure of an MT7-derivative (MT7-diiodoTyr51) allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…Since this toxin can discriminate so well among mAChR subtypes, it would be of general interest for ligand-receptor interactions to uncover the binding mechanism for MT7. It has been shown by site-directed mutagenesis of MT7 that many amino acid residues seem to make up the total binding affinity, and these residues are distributed on all three finger loops of the toxin [17]. Regarding the corresponding sites on the receptor, it can be anticipated that binding contacts with loosely conserved regions are crucially involved in the selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Since this toxin can discriminate so well among mAChR subtypes, it would be of general interest for ligand-receptor interactions to uncover the binding mechanism for MT7. It has been shown by site-directed mutagenesis of MT7 that many amino acid residues seem to make up the total binding affinity, and these residues are distributed on all three finger loops of the toxin [17]. Regarding the corresponding sites on the receptor, it can be anticipated that binding contacts with loosely conserved regions are crucially involved in the selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…4A). Superimposition on other known mamba toxins, MT1 (PDB id: 4DO8 23 ), MT2 (PDB id: 1FF4), MT7 (PDB id: 2VLW 33 ) and ρ-Da1a (PDB id: 4IYE 34 ) showed strong conservation of the backbone (Fig. 4B).…”
Section: Resultsmentioning
confidence: 89%
“…The crystallization trials were carried out using Cryst Chem TM sitting drop vapor diffusion plates with 1 µl drops of protein and precipitant, stored in a constant temperature incubator at 20 °C. Limited screening for crystals was carried out starting from conditions used for MT7 33 . Crystals of AncTx1-W28R/I38S were obtained from 1.9 M ammonium sulfate, 4% MPD, 2% 1,4-dioxane, 2% gamma-valerolactone, 0.132 M sodium citrate, pH 5.5.…”
Section: Methodsmentioning
confidence: 99%
“…The functional expression of mAChRs in BMVECs and bEnd.3 cells was also evaluated by applying agonists/antagonists targeting the allosteric site of the receptors. We found that the selective allosteric M 1 antagonist MT-7 (20 nM) 38 did not exert any inhibitory effect on the ACh-induced calcium signal in either type of brain microvascular endothelial cells (Supplementary Fig. 7A).…”
Section: Resultsmentioning
confidence: 90%